Perencanaan Pendidikan dalam Meningkatkan Kreativitas Belajar Peserta Didik pada Masa Pandemi Covid-19 di MA Nihayatul Amal Rawamerta - Abdurrahman Wahid; Undang Ruslan W; Taufik Mustofa (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2022)
The impact of the Covid-19 pandemic, which has hit almost the entire world, including Indonesia, has been immense and has devastated various sectors of people's lives. The existence of various Government policies to break the chain of transmission from the Covid-19 pandemic is certainly very difficult for the community, especially in carrying out their activities. One of these policies is the Social distancing policy, which clearly makes it difficult for people to carry out their activities. Likewise, in the education sector which was also affected, educational activities in schools had to be carried out online or at home. Many parties are not ready to implement this online education. In the concept of independent learning itself, it is actually the same as government policy, namely independent learning which has the aim of providing a pleasant learning space for students. The context of the Covid-19 pandemic requires schools to carry out their educational planning well and of course they can solve existing problems, including by diverting various educational activities online using various available applications such as : google classroom, zoom, WA group. With the implementation of such an educational plan, it is certainly a new challenge for various parties involved in the educational process at MA Nihayatul Amal Rawamerta Karawang. Basically, the implementation of education planning at MA Nihayatul Rawamerta Karawang runs smoothly even though it is carried out online.